PENGARUH SOSIALISASI PERPAJAKAN, KUALITAS PELAYANAN PAJAK DAN MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP KEPUASAN WAJIB PAJAK ORANG PRIBADI (Studi Kasus Pada PT. Sumberdaya Dian Mandiri Jakarta Pusat) - Agustin Nurdiawati; Nuru Akibah (Jurnal Gici Jurnal Keuangan dan Bisnis, 2021)
In the modern era this year, the Directorate General of Taxes makes it easy for every taxpayer to fulfill obligations in taxation, especially in PPh 21 so that taxpayers feel satisfied in tax services, so this study aims to determine the influence of tax socialization, quality of tax services and modernization of the tax administration system on individual taxpayer satisfaction at PT. Resources Dian Mandiri, Central Jakarta. This study used primary data in the form of questionnaires distributed to individual taxpayers working at PT. Resources Dian Mandiri, Central Jakarta. Convenience sampling method using a sample of 60 respondents. The analysis technique used is multiple linear regression analysis. The collected data was analyzed using the Statistical Product and Service Solution (SPSS) for windows 24.0 program. The results of this study show that partially tax socialization does not have a significant effect on individual taxpayer satisfaction because the value of t count is smaller than t table and significant above 0.05 which is 0.066, while the quality of tax services t count is smaller than t table and significant value of 0.009 which means below 0.05 and has a significant influence on individual taxpayer satisfaction, The modernization of the tax administration system has a significant effect on the satisfaction of individual taxpayers because t count is greater than t table and the significant value is 0.004 below 0.05 which means that the variable modernization of the tax administration system has a significant effect on the satisfaction of individual taxpayers. Simultaneously, tax socialization, tax service quality and modernization of the tax administration system have a significant effect on individual taxpayer satisfaction at PT. Resources Dian Mandiri, Central Jakarta because of the significant value of 0.003 < 0.05.